Analisis Faktor-Faktor yang Memengaruhi Tingkat Kemiskinan di Provinsi Aceh menggunakan Regresi Data Panel - Fitriana AR; Nany Salwa; Sri Wijayanti (Jurnal Peluang, 2023)
Poverty was a fundamental issue of concern for every province in Indonesia, and Aceh was no exception. While the percentage of poor people in Aceh had declined over the last 5 years, Aceh still ranked first of Sumatra with an average poverty rate of 15.70%. In addition, this figure exceeded the national poverty average of 9.96%. People were categorized as poor if they had an average per capita expenditure below the poverty line. One of the ways to overcome poverty was by understanding the factors that influenced it. Research on the poverty rate was not enough if it only focused on one location at a given time. Instead, a study was needed over time to observe the poverty rate across time and individuals. Panel data regression analysis was a regression analysis that used data from several individuals observed over a while. The study aimed to obtain a suitable model for the poverty rate data in Aceh and identified the factors influencing the poverty rate in both Aceh and North Sumatra from 2017 to 2021. The method used was panel data regression, covering 23 districts/cities in Aceh and 33 districts/cities in North Sumatra. The research findings indicated that the appropriate model for the poverty rate was the Random Effect Model with individual effects, with an  value of 68.21%. The study identified three significant independent variables that affected the poverty rate in both Aceh and North Sumatra. The common factor for both provinces was economic growth. However, two distinct factors were observed average years of schooling and life expectancy in Aceh, while population density and open unemployment rate were identified as significant factors in North Sumatra.